The effects of foam rolling as a recovery tool in professional soccer players - Rey, E.; Padron-Cabo, A.; Costa, P. B.; Barcala-Furelos, R. (The Journal of Strength and Conditioning Research, 2017)
Foam rolling (FR) is a common strategy used after training and competition by players. However, no previous studies have assessed the effectiveness of FR as recovery tool in sports populations. The aim of this study was to examine the effectiveness of FR (20 minutes of foam rolling exercises on quadriceps, hamstrings, adductors, gluteals, and gastrocnemius) and passive recovery (20 minutes sit on a bench) interventions performed immediately after a training session on Total Quality Recovery (TQR), perceived muscle soreness, jump performance, agility, sprint, and flexibility 24 hours after the training. During 2 experimental sessions, 18 professional soccer players (age 26.6 ± 3.3 years; height: 180.2 ± 4.5 cm; body mass: 75.8 ± 4.7 kg) participated in a randomized fully controlled trial design. The first session was designed to collect the pre-test values of each variable. After baseline measurements, the players performed a standardized soccer training. At the end of training unit, all the players were randomly assigned to the FR recovery group and the passive recovery group. A second experimental session was carried out to obtain the posttest values. Results from the between-group analyses showed that FR had a large effect on the recovery in agility (Effect Sizes [ES]= 1.06), TQR (ES= 1.08), and perceived muscle soreness (ES= 1.02) in comparison to passive recovery group at 24 h post-training. Thus, it is recommended soccer coaches and physical trainers working with high-level players use a structured recovery session lasting from 15 to 20 min based on FR exercises that could be implemented at the end of a training session to enhance recovery between training loads.